Drop jumps versus sled towing and their effects on repeated sprint ability in young basketball players - Zagatto, Alessandro M. [UNESP]; Claus, Gabriel M. [UNESP]; Dutra, Yago M. [UNESP]; de Poli, Rodrigo A. [UNESP]; Lopes, Vithor H. F. [UNESP]; Goodall, Stuart; Loturco, Irineu; Boullosa, Daniel (Springer Nature, 2022)
Background: The aim of the investigation was to compare the occurrence of post-activation performance enhancement (PAPE) after drop jumps, or heavy sled towing, and the subsequent effect on repeated sprint ability (RSA). Methods: Ten young basketball players (17 ± 1 yrs) performed, in randomized order, RSA test with changes of direction after a standardized warm up followed by drop jumps, heavy sled towing, or no exercise (control condition). Neuromuscular assessments composed of two maximal voluntary contractions of the knee extensors, peripheral nerve stimulation, and surface electromyography (EMG), responses were recorded before and immediately after the RSA. The EMG signal of leg muscles during sprinting were also recorded as well as the blood lactate concentration. Results: The drop jumps improved the RSA mean time (P = 0.033), total time (P = 0.031), and slowest time (P = 0.029) compared to control condition, while heavy sled towing did not change RSA outcomes (P > 0.05). All conditions exhibited a decrease of doublet high frequency stimulation force (pre-post measurement) (P = 0.023) and voluntary activation (P = 0.041), evidencing the occurrence from peripheral and central components of fatigue after RSA, respectively, but no difference was evident between-conditions. There was a significantly greater EMG activity during sprints for the biceps femoris after drop jumps, only when compared to control condition (P = 0.013). Conclusion: Repeated drop jumps were effective to induce PAPE in the form of RSA, while heavy sled towing had no effect on RSA performance in young basketball players. Furthermore, both conditioning activities exhibited similar levels of fatigue following the RSA protocol. Thus, drop jumps may be used as an alternative to induce PAPE and thus improve performance during sprints in young male basketball players.
Keywords: Neuromuscular fatigue; Physical fitness; Post-activation performance enhancement; Post-activation potentiation; Sport